Analisis Nilai Clothing Time, Prothrombine Time dan Activated Partial Thromboplastine Time pada Remaja Obes - Nelly Nelly; Mansyur Arief; Ilham Jaya Patellongi (Universitas Muhammadiyah Semarang, 2018)
Analysis of the Value of Clothing Time, Prothrombine Time and Activated Partial Thromboplastine Time in Obese AdolescentsLatar belakang: Berdasarkan estimasi WHO, obesitas menjadi masalah kesehatan di dunia. Selain karena insidennya meningkat,juga karena obesitas menimbulkan berbagai komplikasi penyakit metabolik dan vaskuler seperti sindrom metabolik, penyakit jantung, stroke dan gangguan pembekuan darah. Mengingat insiden obesitas pada saat ini telah mengalami pergeseran dari dewasa ke usia anak dan remaja serta berbagai komplikasi yang ditimbulkan oleh obesitas itu sendiri maka dianggap perlu dilakukan deteksi dini adanya gangguan hemostasis pada obesitas usia anak dan remaja untuk mencegah komorbiditas obesitas dikemudian hari.Metode: Desain penelitian ini adalah cross sectional study yang dilakukan di SMA Katolik Rajawali Makassar dengan menggunakan sampel siswa yang berumur sekitar 10-18 tahun. Dilakukan pemeriksaan antropometrik dan pemeriksaan nilai Clothing Time (TT), Prothrombine Time (PT) dan Activated Partial Thromboplastine Time(aPTT). Obesitas dinyatakan berdasarkan Kategori IMT yang ditentukan berdasarkan ambang batas Z-Score sedangkan kategori lingkar pinggang ditentukan berdasarkan Waist Circumfrence for Hong Kong Chinese Children (2008). Data dianalisis dengan independent t-test untuk menilai perbedaan nilai CT, PT dan aPTT pada remaja obes dan berat badan normal sedangkan uji korelasi pearson digunakan untuk melihat adanya hubungan antara IMT dan LP dengan nilai CT, PT dan aPTT pada remaja obes. Subyek adalah siswa siswi SMA Katolik Rajawali Makassar dengan rerata umur 15 tahun terdiri dari 33 orang laki-laki (22 obesitas,11 normal) dan 16 perempuan (5 obesitas,11 normal).Hasil: Didapatkan perbedaan bermakna antara nilai CT, PT dan aPTT pada remaja obes dan berat badan normal. Nilai rata-rata CT, PT dan pada kelompok normal adalah masing-masing aPTT 11±1,23; 13,86 ± 0,63 detik ; 32,90 + 1,77 detik dan pada kelompok obes adalah nilai CT,PT dan aPTT adalah 9 ±1,7; 13,11 + 0,59 detik dan 31,92+3,82 detik. Selain itu, terdapat korelasi negatif antara nilai CT,PT dan LP pada remaja obes namun tidak ditemukan adanya korelasi antara IMT dan LP dengan nilai aPTT pada remaja obes. Nilai CT, PT dan aPTT pada remaja obes cenderung memendek dibandingkan dengan berat badan normal.Simpulan: Semakin tinggi nilai IMT dan LP, maka nilai CT, PT dan aPTT semakin memendek. Background: Based on World Health Organization estimation, obesity has been a world health problem. Aside from the increased incident, also because obesity causes various vascular and metabolic disease complications such as metabolic syndrome, heart disease, stroke and blood coagulation disorder. Considering that the obesitysyndrome now has shifted from adults to kids and adolescent along with the complications of obesity, it is necessary to get an early detection in haemostaticdisorder in kids and adolescent obesity to prevent obesity co morbidity in the future. Method: The design of the research is cross sectional study which was carried out the population of Katolik Rajawali High School student in Makassar, ranging in age from ten to eighteen years old. An anthropometric examination was done, as well as examination of Clothing Time (TT), Prothrombine Time (PT) and Activated Partial Thromboplastine Time (PTT) value. Obesity is declare based on Body Mass Index (BMI) Category which was determined based on Z-Score threshold whereas waist line category was determined based on Waist Circumference (WC) for Hong Kong Chinese Children (2008). Data was analyzed using an independent t-test to assess the difference in CT, PT and aPTT value in obese adolescent and normal weight whereas the Pearson correlation test was used to see the relation between BMI and WC with CT, PT and aPTT in obese adolescent. Subjects were the high school students with the average age of 15 years old, consisting of 33 boys (22 obese, 11 normal) and 16 girls (5 obese, 11 normal). Result: The results showed significance different between CT, PT and aPTT value in obese adolescent and normal weight. The mean CT, PT and aPTT in the normal group were each 11 ± 1.23; 13.86 ± 0.63 seconds; 32.90 + 1.77 seconds and in the obese group the CT value, PT and aPTT were 9 ±1.7; 13.11 + 0.59 seconds and 31.92 + 3.82 seconds. Besides that, there was a negative correlation between CT, PT and WC value in obese adolescent but there was no correlation between BMI and WC with aPTT value in obese adolescent. Clothing Time, PT and aPTT value in obese adolescent tends to shorten compared to normal weight. Conclusion: The higher BMI and WC values, the shorter CT, PT and aPTT values. Keywords : Obesity, adolescent,CT, PT,aPTT